Clays and Clay Minerals, Vol. 56, No. 6, 633–644, 2008. - Ayala-luis, Karina Barbara; Koch, Christian Bender; Hansen, Hans Christian Bruun (The Clay Minerals Society, 2008)
Mixed FeIIFeIII hydroxides, commonly referred to as ‘green rusts’ (GRs), are important reactive phases in both man-made and natural geochemical systems. Determinations of the standard Gibbs energy of formation of GRs are needed to understand and predict the occurrence and possible reactions of GRs in these systems. Slow acid titrationof crystalline greenrust sulfate (GRSO4 ) with the formationof magnetite was used as a novel method to determine the standard Gibbs energy of formation of GRSO4 ,DfGo(GRSO4 ). Aqueous suspensions of GRSO4 , with pH slightly >8, were titrated slowly with 1 M H2SO4 until pH = 3 under strict anoxic conditions. Powder X-ray diffraction and Mo¨ ssbauer analysis revealed that magnetite was the only solid phase formed during the initial part of the titration, where the equilibrium pH was maintained above 7.0. The ratio of Fe2+ release to consumption of protons confirmed the stoichiometry of dissolutionof GRSO4 and the formation of magnetite at equilibrium conditions. The estimate of the absolute value of DfGo(GRSO4 ) was -3819.43D6.44 kJ mol-1 + y6[DfGo(H2O(l))], where y is the number of interlayer water molecules per formula unit. The logarithm of the solubility product, log Ksp, was estimated to be -139.2D4.8 and is invariable with y. Using the new value for DfGo(GRSO4 ), the reductionpoten tials of several GRSO4 -Fe oxide couples were evaluated, with the GRSO4 -magnetite half cell showing the smallest redox potential at pH 7 and free ion activities of 10-3.
The Standard Gibbs Energy Of Formation Of Fe(ii)fe(iii) Hydroxide Sulfate Green Rust
gsccm56604-aya.pdf - 291KB
Keywords: Periodicals; Geology; Acid Titration; Gibbs Energy of Formation; Green Rust; Layered Double Hydroxides; Magnetite; Mossbauer Spectroscopy; Solubility Product